Characterization of Pathogenic Bacteria Causing Bacterial Wilt Disease of Kepok Banana in Manokwari, West Papua - Mogea, Rina; Puspasari, Aninda; Ruimassa, Reymas M R (School of Life Sciences and Technology, Institut Teknologi Bandung, 2025)
Kepok bananas, including their processed derivatives, serve as a vital alternative staple food alongside rice and contribute significantly to food security, particularly in the Manokwari region. Maintaining the health of banana plants is essential for preserving global food diversity. Ensuring their sustainable availability is crucial; however, this is increasingly threatened by the emergence of banana diseases. The rapid spread of banana diseases was first reported in 2018 in the SP IV Bowi Subur area of Masni District, and by 2019, similar cases were documented in the Anday area of South Manokwari District. This study aims to isolate and identify the pathogenic bacteria responsible for banana diseases in Kepok bananas from the Anday region of South Manokwari, using morphological and biochemical characterization. The macroscopic characteristics of the four isolates revealed a circular shape with entire margins, a convex surface, and a maroon coloration when cultured on CPG medium. Gram-staining analysis indicated that the bacterial cells were gram-negative and exhibited a short bacillus morphology. Isolation from samples collected from the banana rhizosphere, pseudostems, and fruits yielded four distinct isolates, designated as AR1, APS1, AR2, and ABF2. Based on nitrate reduction and gelatin hydrolysis tests, isolates AR1, AR2, and ABF2 were identified as belonging to the Blood Disease Bacterium (BDB), specifically Ralstonia syzygii phylotype IV (Indonesia), which has undergone taxonomic reclassification as Ralstonia syzygii subsp. celebesensis. This disease can result in crop losses exceeding 50% when it spreads within a consortium. In contrast, the APS1 isolate could not be conclusively identified as either R. syzygii subsp. celebesensis or R. solanacearum.